2020
DOI: 10.33963/kp.15172
|View full text |Cite
|
Sign up to set email alerts
|

Watchman FLX: the initial Polish experience with a new device for left atrial appendage occlusion

Abstract: other bleedings (n = 6); stroke during treatment with OACs or non-vitamin K antagonist oral anticoagulants (NOACs; n = 5); and other absolute contraindications to OAC or NOACs (n = 3). The most common LAA morphology was broccoli (n = 22), chicken-wing (n = 7), windsock (n = 7), and other (n = 3). All LAA closure procedures were done under general anesthesia with vascular access from the femoral vein. Transseptal puncture was undertaken under transesophageal echocardiography (TEE) guidance. Next, the Watchman T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…In this regard, the novel Watchman Flex has been designed to provide an improved conformability, a full or partial recapture during implant, better device stability and maneuverability within the appendage as well as a shorter length and wider sizing matrix to treat a wider variety of anatomies. These technical characteristics have clearly influenced the technical success first observed in the PINNACLE ( 8 ) and in the studies from Korsholm et al ( 9 ), Grygier et al ( 10 ) and Cruz-González et al ( 11 ) and now confirmed by our data. In addition, no intraprocedural device embolization occurred.The innovative design with two rows of anchors and the possibility to fully recapture and reposition the device allowing for optimal deployment are both aspects that may have contributed to this remarkable outcome.…”
Section: Discussionsupporting
confidence: 86%
“…In this regard, the novel Watchman Flex has been designed to provide an improved conformability, a full or partial recapture during implant, better device stability and maneuverability within the appendage as well as a shorter length and wider sizing matrix to treat a wider variety of anatomies. These technical characteristics have clearly influenced the technical success first observed in the PINNACLE ( 8 ) and in the studies from Korsholm et al ( 9 ), Grygier et al ( 10 ) and Cruz-González et al ( 11 ) and now confirmed by our data. In addition, no intraprocedural device embolization occurred.The innovative design with two rows of anchors and the possibility to fully recapture and reposition the device allowing for optimal deployment are both aspects that may have contributed to this remarkable outcome.…”
Section: Discussionsupporting
confidence: 86%
“…Lastly, a single-center registry that enrolled 38 patients with high-risk features also reported a 100% technical success rate with this device, with outstanding safety and efficacy results at 3month follow-up [11].…”
Section: Drtmentioning
confidence: 92%
“…Smaller LAAC registries with Watchman FLX have already been published, presenting some limitations: namely small series, focus on imaging guidance, several enrolling centers with low inclusion rates and different levels of experience, and a high rate of "non-FLX" devices used for LAAC compromising the consecutiveness of data collection. [14][15][16] A recent dual-center study from Galea et al 17 In both the enrolling centers involved in our registry, the Watchman FLX represented the main LAAC device, used in more than 95% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The two centers involved in our registry boast a solid practice in invasive cardiology procedures, with high‐volume experience in LAAC techniques. Smaller LAAC registries with Watchman FLX have already been published, presenting some limitations: namely small series, focus on imaging guidance, several enrolling centers with low inclusion rates and different levels of experience, and a high rate of “non‐FLX” devices used for LAAC compromising the consecutiveness of data collection 14–16 . A recent dual‐center study from Galea et al 17 (WATCH‐DUAL study) compared the two generations of Watchman devices in a smaller cohort of 144 patients (n. 71 Watchman 2.5 and n. 73 FLX); compared to the previous generation, Watchman FLX was associated with improved sealing properties (higher LAA coverage) and lower DRT (at 45 days computed tomography scan and TEE), despite no differences resulted in terms of clinical outcomes (procedure‐related complications and 6‐months net adverse cardiovascular events).…”
Section: Discussionmentioning
confidence: 99%